A tanítványok ördögűzési, halottfeltámasztási szolgálata és szenvedése - LÉSZAI, Lehel (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2021)
The Disciples’ Ministry of Exorcism, Resurrection of the Dead, and Suffering. Service meant exorcism besides preaching and healing. According to Mk 3:15, Jesus calls his disciples so that they would be with him, preach the gospel, and exorcise demons. The authority of the disciples over unclean spirits (Mk 6:7) refers to their sharing in Jesus’s mission (Mk 1:22.23.27). Exorcism promoted the expending of God’s kingdom and the weakening of Satan’s power. In Mk 6:7, Jesus mentions exorcism as a concrete task for his disciples, what was fulfilled by them (6:7). We can learn from Mt 9:8 and 10:1 that the disciples were entrusted with power to cast out demons. Lk 9:1 mentions the same command. According to the report of Luke, the seventy(-two) disciples cast out demons too, although they did not receive explicit command for this in 10:9. Matthew is the only one who mentions that Jesus ordered his disciples to raise the dead (Mt 10:8). Thus, this belonged to the ministry too. The synoptic gospels do not mention anywhere that the disciples would carry out this command. But several reports mention that Jesus raised people from the dead. He answered the question that John the Baptist transmitted by his disciples by saying that the dead are raised up (Mt 11:5), so he truly carried this out as well. Some congregations of the early church had some difficulties with this command. The book of Acts reports in two cases that the disciples used this exceptional gift (Acts 9:36ff and 20:7ff). In order that the possession of this important power would not cause them any harm, when using this gift, the disciples were to ask nothing in return. Service is connected with suffering because mission supposes both. Jesus came to serve and suffer among the people, which is why he prepares his disciples for the future suffering. The disciples do share in Jesus’s mission, in his power and his authority, but in his destiny too. Following includes breaking with the family and profession, giving up the possessions, homelessness, self-denial, bearing the cross, persecution, and suffering. Mark’s congregation was persecuted. Therefore, it was a consolation for them that Jesus had suffered earlier and finished victoriously the battle against death. Jesus did not conceal the reality from his disciples and warned them that they had to flee too, they might be whipped and some of them might be executed because all of these form part of the mission. To follow him did not mean to study the Torah under his direction but to identify with his suffering.